P-36 Quadriceps muscle fatigue after 2000-m rowing. (18th November 2016) - Husmann, F; Gube, M; Felser, S; Weippert, M; Mau-Moeller, A; Bruhn, S; Behrens, M
Abstract : Introduction: Despite extensive investigations on the task-dependency of neuromuscular fatigue after several types of exercise, hardly anything is known about central and peripheral factors of fatigue after rowing. In rowing, approximately 70% of total muscle mass is involved due to the fact that upper and lower body muscles work synchronised during the rowing stroke. 1 In particular, the quadriceps muscle is identified as a major contributor to propulsion of the rowing boat by pushing against the foot stretcher. 2 The aim of the present study was to investigate the effect of a 2000-m rowing time-trial on indices of quadriceps muscle fatigue. Methods: Eight competitive rowers (4 males, 4 females, 20 ± 4 years) performed a 2000-m time-trial on an indoor rower and a control condition (sitting). Neuromuscular function of the quadriceps muscle was analysed before and after each experimental condition. Maximal voluntary torque, voluntary activation estimated via interpolated twitch technique and normalised root mean square of the EMG signal (RMS·M –1 ) were assessed during maximal voluntary contractions (MVCs). Furthermore, potentiated quadriceps twitch torque and maximal M-wave amplitudes in response to electrical nerve stimulation were recorded. Results: After 2000-m rowing, there were significant reductions in isometric and concentric maximal voluntary torque (–20%–18%, P < 0.01). Both voluntary activation during isometric and concentric MVCs were significantly decreased after rowing ( P < 0.05). However, there was no significant change in quadriceps twitch torque after rowing. For the control condition, indices of central and peripheral fatigue were not significantly different from baseline values (all P > 0.05). Discussion: The 2000-m rowing time-trial induced considerable quadriceps muscle fatigue. Data further revealed a major contribution of central factors to quadriceps muscle fatigue after rowing as indicated by significant reductions in voluntary activation and quadriceps RMS·M –1 . Interestingly, previous studies have typically shown that less central, but rather peripheral mechanisms contribute to quadriceps muscle fatigue after short-duration endurance exercise [3]. We hypothesise, in this regard, that the strong impairments in voluntary drive to quadriceps are possibly related to a "spill-over" of central fatigue from the great amount of simultaneously working muscles. This effect might be attributable to the ensemble feedback of inhibitory group III/IV muscle afferents. 4 References: Steinacker J. J Appl Physiol 1993;84 :3–10. Soper C, Hume PA. Sports Med 2004;34 :825–48. Thomas K, et al . Med Sci Sports Exerc 2015;47 :537–46. Sidhu SK, et al . J Physiol 2014;592 :5011–24.